Hubungan intelligence quotient dengan perceived stress pada mahasiswa Fakultas Kedokteran Universitas X - Bolang, Jenifer; Pali, Cicilia; Sinolungan, Jehosua Samratson Victor (UNIVERSITAS SAM RATULANGI, 2024)
Background: Every medical student has a different level of intelligence quotient (IQ), where IQ they have will help in solving problems, especially in learning. Problem based learning (PBL), expert lectures, and skills lab are some of the things that a medical student will do when studying at the faculty of medicine. This can be a stressor for a medical student who is living his life within the scope of the faculty of medicine. This is supported by data that proves that medical students have high levels of stress, where the average stress level is in the moderate stress category. Aim: To determine the relationship between IQ and perceived stress (PS) in medical faculty students at University of X. Methods: This research is a quantitative study with a cross sectional design involving 162 respondents. Results: This research shows that there are 57.4% of students who have an average IQ level and a PS level in the moderate PS category of 70.4%. Where the two variables have a very weak correlation when tested with the Spearman rank test with a correlation coefficient value of 0.184. Conclusion: Students at the Faculty of Medicine at X University has an average IQ level and moderate PS level with a very weak correlation between the two variables. Keywords: medical students, intelligence quotient, perceived stress